Regional Agreements and Trade Services : Policy Issues - Mattoo, Aaditya (World Bank, Washington, D.C., 2013)
Every major regional trade agreement now has a services dimension. Is trade in services so different that there is need to modify the conclusions on preferential agreements pertaining to goods reached so far? The authors first examine the implications of unilateral policy choices in a particular services market. They then explore the economics of international cooperation and identify the circumstances in which a country is more likely to benefit from cooperation in a regional rather than multilateral forum.